Physico-Chimical characterisation of some samples of honey produced in north - east of Algeria - khalifa Fatma (My University, 2024)
Honey is a sticky substance or also known as bee saliva, a substance made by beesfromthenectarofflowersandplants whichhasnothingtodowithhumans. Therearearound 320 typesofhoneywhicharenotsubject toanycontrolsand asaresult .consumersareexposedtoanumberofhealthhazards Inthis context, thisstudywas carried outwiththe aimoffindingaproposalfor .Algerianstandardsforhoneyqualitycontrol The study focused on 23 samples of honey collected in north-east Algeria (Souk-Ahras,Tébessa,Guelma)inadditiontoanimportedsampledisplayedontheAlgerianmarket,inordertodeterminetheircharacteristicsandcompare themwiththerestof .thesaples: Determinephysico-chemicalproperties suchasaciditypercentage, electrolytepercentage, water percentage, protein percentage, quantitative pollen analysisWiththeaimofidentifyingtheirconformityornon-conformitywiththescale .proposedbyinternationalorganisationsforhoneyqualitycontrol Analysisoftheresultsshowsthatthehoneysamplescollectedwereofgoodquality .andcompliedwithinternationalstandards ------------------------------------------------------------------------------------------------------------------------- العسل عبارة عن مادة لزجة أو ما يعرف بلعاب النحل، وهي مادة يصنعها النحل من رحيق األزهار ، يوجد عدة انواع من العسل لكن لا تخضع لاي ضوابط، ونتيجة لذلك يتعرض المستهلكون لعدد من المخاطر الصحية وفي هذا السياق تم إجراء هذه الدراسة بغرض إيجاد مقترح لمعايير جزائرية لمراقبة جودة العسل ركزت الدراسة على 23 عينة من العسل التي تم جمعها في شمال شرق الجزائر (سوق أهراس، تبسة، قالمة) .بالاضافة إلى عينة مستوردة معروضة في السوق الجزائرية، وذلك لتحديد خصائصها ومقارنتها مع باقي العينات حيث تم تحديد الخصائص الفيزيائية و الكيميائية ( نسبة الحموضة , نسبة اإللكتروليت, نسبة الماء, نسبة البروتين, التحليل الكمي لحبوب اللقاح ,كمية الرمادو اللون ) .بهدف تحديد مدى مطابقتها أو عدم مطابقتها للمقياس المقترح من قبل المنظمات الدولية لمراقبة جودة العسل أظهر تحليل النتائج أن عينات العسل التي تم جمعها كانت ذات نوعية جيدة ومطابقة للمعايير الدولية ما عدا العينة .المستوردة والمعروضة في السوق الجزائرية لم تكن مطابقة للمعايير ------------------------------------------------------------------------------------------------------------------------- Lemielestunesubstancecollanteouaussiappeléesalived'abeille,unesubstancefabriquéeparlesabeillesàpartirdunectardesfleursetdesplantesquin'arienàvoiravecl'homme,etilexisteenviron320typesdemielquinesontsoumisà .aucuncontrôleetparconséquentleconsommateurestexposéàplusieursdangerspourlasanté Danscecontexte,cetravailaétéréalisédanslebutdetrouverunepropositiondenormesalgériennespourlecontrôlede .laqualitédumiel Cetteétude aportésur23 échantillonsdemielcollectésdans lenord-estalgérien(SoukAhras,Tébessa,Guelma) en plusd'unéchantillonimportéexposédanslemarchéalgérienafindedéterminerleurscaractéristiquesetdelescompareravec .lerestedeséchantillons Déterminerlespropriétésphysico-chimiquestellesquelepourcentaged'acidité,lepourcentaged'électrolytes,lepourcentaged'eau,lepourcentagedeprotéines,l'analysequantitativedupollen Dontlebutd’identifierleurconformitéounon-conformitéavecl'échelleproposéeparlesorganisationsinternationales .pourlecontrôledelaqualitédumiel L’analysedesrésultatsobtenusmontrequeleséchantillonsdemielcollectésdebonnequalitésetonconformitéavecles .normesinternationales